Determinant of Financial Performance of Islamic Credit and Financing Union (KSPPS) in Salatiga - Ashari, Teguh; Widiyanto, Widiyanto; Yulianto, Arief (Journal of Economic Education, 2018)
The high growth of Islamic Credit and Financing Union (KSPPS) in Indonesia encounters several problems, and one of which is financial performance. This study attempts to uncover the factors influencing financial performance of Islamic Credit and Financing Union (KSPPS) in Salatiga using Pecking Order Theory (POT) inits analysis. POT explains how company’s preference uses fund in doing their operational activity. The expected factors influencingIslamic Credit and Financing Union (KSPPS)’s financial performance are Capital Adequacy Ratio (CAR), Non Performing Finance (NPF), Financing to Deposit Ratio (FDR), Operating Expenses-Operating Income (OEOI), and capital structure. The analysis methodology of this study is multiple panel regression employing software Eviews 9. The result of regression test shows that OEOI affects partially towards Return on Asset (ROA). In contrast, the other factors such as CAR, NPF, and capital structure do not have any significant influence towards ROA. The differencesbetween this study and previous studies are on the city-scopefinancial data of Islamic Credit and Financing Union (KSPPS) and the use of POT implemented to explain financial performance.